PENERAPAN AKAD IJARAH DALAM PRODUK PEMBIAYAAN BANK SYARIAH - Devianita, Devianita (Prodi Ekonomi Syariah Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
All kind of business that e person runs will not escape the Ijaroh (lease) contranc. The aplication of the Ijarah contract in business matters in the form of renting land, buildings,sevices, and others.In busness matters,problems often arise in Ijarah contract, as well as in Islamic Banks.Responding this problems, this journal specifically provides solution and information in the form of understanding Ijarah contract carried out by Islamic banks.With the diskriptive analisys menthode, this study explains the concept of the Ijarah contranct in the form of the nation of Ijarah,legal basis,harmony and requirement,various kinds of ijarah, payment of salaries and rent, cancellation and expiration of ijaroh contranc to islamic bank product.